Pengaruh Amelioran terhadap Jerapan Isotermal Fosfat di Tanah Mineral Masam: Effect of Ameliorant on Isothermal Phosphate Sorption in Acid Mineral Soil - Maulida Maulida; Fadly Hairannoor Yusran; Ismed Fachruzi; Zuraida Titin Mariana (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2025)
Ultisol is one type of land in Indonesia that has an area distribution of about 25% of Indonesia's total land area and the widest distribution is in Kalimantan (21.938.000 ha). The acidic pH of the soil causes low availability of P in Ultisol and the occurrence of P fixation by Al and Fe which are positively charged, making P difficult to be available to plants. In this study, ameliorant was added in the form of dolomite and chicken manure to see the effect on Ultisol soil by isothermal phosphate absorption analysis and processed using the Langmuir, Freundlich, and Brunauer-Emmett-Teller (BET) equations. The results of the study concluded that the application of P on Ultisol soil in Gunung Kupang Village, Cempaka District, Banjarbaru City, was in accordance with the Freundlich Equation. High or low P absorption indicates the level of P availability in the soil. In other words, fixation on acidic mineral soils can reduce the amount of P available to Plants.